SAT0553 Anti-Interleukin-1 Therapies and Pregnancy Outcome: an International Cohort. (9th June 2015) - Youngstein, T.; Lane, T.; Rowczenio, D.; Ozdogan, H.; Ugurlu, S.; Hoffmann, P.; Riminton, S.; Headley, A.P.; Ryan, J.; Harty, L.; Roesler, J.; Blank, N.; et al.
Abstract : Background: Women with auto-inflammatory disease on long-term IL-1 blockade increasingly ask about the safety and outcomes of pregnancy but little data is available. Objectives: To analyse the outcomes of pregnancy in women on long-term anti-IL-1 therapy. Methods: We obtained the clinical details and pregnancy outcomes of women exposed to anti-IL-1 agents in 7 countries. Results: We identified 13 women aged 16 – 38 years, with a total of 15 pregnancies exposed to IL-1 blockade. 9 women had CAPS, 2 Adult Onset Stills Disease, 1 TRAPS, 1 FMF and 1 Idiopathic Pericarditis. 4 received canakinumab, 2 stopped treatment after conception, 2 switched to anakinra. 13 foetuses were exposed to anakinra. 3 women started anakinra during pregnancy, 3 stopped treatment following conception. All pregnancies were completed. The shortest term was 35 weeks. APGAR score was 9-10 at 10 mins in all cases. Birth weight range 2.02-3.94 kilos. 5 were breast fed for 3 – 40 weeks. Age at last contact was from 1 week – 8 years. Only 1 child had developmental abnormalities; growth hormone deficiency due to ectopic neurohypophysis and unilateral renal agenesis. We also identified 11 children with paternal exposure to anti-IL-1 therapies, all developmentally normal to date. Conclusions: These successful pregnancies significantly extend our knowledge of pregnancy outcomes in parents receiving anti-IL-1 therapies. A co-author has previously reported the intrauterine death of a foetus (of a twin pregnancy) with bilateral renal agenesis exposed to anakinra. The surviving twin is developmentally normal. Although numbers are small the data provide reassurance to physicians caring for these patients. The relationship between IL-1 inhibition and renal agenesis requires further study. Each pregnancy should be assessed and risks and benefits of maintaining therapy individually discussed with potential parents. Disclosure of Interest: None declared